LEXICAL-SEMANTIC STUDY OF METONYMS IN ENGLISH AND UZBEK LANGUAGES - Yusupov Muhammadsodiq Rizomat o'g'li (TADQIQOTLAR, 2025)
Abstract: Metonymy, as a figure of speech and a semantic mechanism, plays a pivotal role in language, allowing speakers to express concepts through part-whole, cause-effect, or contiguity relationships. This article investigates the lexical-semantic characteristics of metonyms in English and Uzbek languages, emphasizing their structural, semantic, and functional properties. Using descriptive, contrastive, and analytical methods, the study examines authentic texts, dictionaries, and corpora to identify patterns of metonymic expression and explore language-specific realizations. The research reveals that both English and Uzbek employ metonymy extensively in various domains, including daily communication, literature, and professional discourse. English metonyms often rely on conventionalized idiomatic expressions and lexicalized forms (the crown to refer to monarchy, Hollywood for the film industry), whereas Uzbek utilizes morphologically and syntactically explicit structures, often drawing on culturally salient imagery (to‘qimachi markazi – “center of textile production” to denote the textile industry). The study also highlights how metonymic relations contribute to cognitive economy, textual cohesion, and expressive richness. Comparative analysis demonstrates that while English and Uzbek share universal cognitive principles in establishing part-whole or associative relations, cultural and typological differences shape their linguistic realization. The findings have practical implications for translation, lexicography, and language teaching, emphasizing the importance of understanding metonymy for accurate interpretation, cross-linguistic mapping, and effective communication.